Evaluasi Komprehensif Penerapan Balanced Scorecard untuk Pengukuran Kinerja Organisasi: Tinjauan Literatur - Junaidi Efendi; Achmarul Fajar; Ria Kasanova (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This article presents a comprehensive evaluation of the application of the Balanced Scorecard (BSC) as an organisational performance measurement tool through a review of recent literature. The BSC, developed by Kaplan and Norton, is a strategic management system that links an organisation's long-term goals with relevant performance measures. This research aims to assess the effectiveness of BSC in improving organisational performance in various sectors, both public and private, and identify the challenges and advantages associated with its implementation. Through an analysis of recent studies and articles, the findings show that BSC can improve communication and collaboration between departments, and encourage employee engagement. However, challenges in setting the right indicators and resistance to change remain barriers to implementation. The article also provides recommendations for managers and practitioners in improving the effectiveness of BSC, including the importance of training, top management support, and tailoring the BSC system to the organisational context. Thus, the results of this study contribute to a better understanding of the BSC and its implications for organisational performance measurement.